An observational near-infrared spectroscopy study on cerebral autoregulation in post-cardiac arrest patients: Time to drop 'one-size-fits-all' hemodynamic targets?. (May 2015) - Ameloot, K.; Genbrugge, C.; Meex, I.; Jans, F.; Boer, W.; Vander Laenen, M.; Ferdinande, B.; Mullens, W.; Dupont, M.; Dens, J.; DeDeyne, C.
Abstract: Aims: A subgroup of patients with ROSC after cardiac arrest (CA) with disturbed cerebral autoregulation might benefit from higher mean arterial pressures (MAP). We aimed to (1) phenotype patients with disturbed autoregulation, (2) investigate whether these patients have a worse prognosis, (3) define an individual optimal MAP per patient and (4) investigate whether time under this individual optimal MAP is associated with outcome. Methods: Prospective observational study in 51 post-CA patients monitored with near infrared spectroscopy. Results: (1) 18/51 patients (35%) had disturbed autoregulation. Phenotypically, a higher proportion of patients with disturbed autoregulation had pre-CA hypertension (31 ± 47 vs 65 ± 49%, p  = 0.02) suggesting that right shifting of autoregulation is caused by chronic adaptation of cerebral blood flow to higher blood pressures. (2) In multivariate analysis, patients with preserved autoregulation ( n  = 33, 65%) had a significant higher 180-days survival rate (OR 4.62, 95% CI [1.06:20.06], p  = 0.04]. Based on an index of autoregulation (COX), the average COX-predicted optimal MAP was 85 mmHg in patients with preserved and 100 mmHg in patients with disturbed autoregulation. (3) An individual optimal MAP could be determined in 33/51 patients. (4) The time under the individual optimal MAP was negatively associated with survival (OR 0.97, 95% CI [0.96:0.99], p  = 0.02). The time under previously proposed fixed targets (65, 70, 75, 80 mmHg) was not associated with a differential survival rate. Conclusion: Cerebral autoregulation showed to be disturbed in 35% of post-CA patients of which a majority had pre-CA hypertension. Disturbed cerebral autoregulation within the first 24 h after CA is associated with a worse outcome. In contrast to uniform MAP goals, the time spent under a patient tailored optimal MAP, based on an index of autoregulation, was negatively associated with survival.